Clinical testing of propofol geriatic dose for sedation designed via in silico trial. Issue 132 (August 2016) - Gallardo-Hernandez, Ana Gabriela; Hernandez-Perez, Ana Luisa; Ordoñez-Espinosa, German; Sanchez-Lopez, Antonio; Revilla-Monsalve, Cristina; Islas-Andrade, Sergio
Highlights: Anesthesia for patients older than 65 years represents more risk due to age-related physiological changes and the multiple co-morbidities they often present. A computer simulation study showed that lower than conventional doses of propofol were adequate to sedate the elderly. A clinical trial validated the new dose scheme. Using a lower dose in the elderly minimizes the secondary effects of propofol. Abstract: The geriatric population shows significant physiological changes due to aging and the multiple co-morbidities that they often present. Conventionally the propofol sedation dose for patients older than 65 years is 80% of the adult dose. We performed an in silico trial for elderly population and the results showed that the necessary simulated dose of propofol was lower than the conventional dose; therefore, a clinical trial was implemented to test three different propofol doses, two of them lower than the conventional dose, during a pacemaker implantation. The clinical trial showed that there was no clinical difference between the effects of the doses. A BIS monitor was used to measure the level of sedation, which proved to be adequate and well maintained by all patients. All the patients maintained an acceptable level of sedation, measured by a BIS monitor. Since propofol has some dose-dependent secondary effects, the use of lower doses, especially the ones designed for this age group, helps to avoid them.